Ruffles and the cozy, cozy bed - Melling, David (Ruffles, 2023)
Ruffles loves a lot of things, like digging, running, and sleeping. He does not love loud noises, especially at night. When Ruffles sees a flash and hears a loud bang, he knows that can only mean one thing: a thunderstorm! But there's no place in the house that feels like just the right hiding spot from the storm outside. Hiding places should be quiet, safe, and most of all, cozy. That's when Ruffles realizes the best place to be is his very own bed where the loud noises--and the storm--don't feel so scary.